Topsoil Magnetic Susceptibility and Heavy Metal Contamination: A Case Study in Al-Muthanna Province, Iraq - Ameen, Nawrass (Iraqi Journal of Science, 2020)
Due to rapid urbanization and industrialization that occurred in Al- Muthanna province in southeastern Iraq during the last decade, pollutants such as heavy metals were emitted into the environment and became a serious threat to human health. Environmental pollution could be caused by different types of pollutants, which come from different sources. This study aims to assess the environmental magnetism efficiency for heavy metal pollution assessment using the magnetic susceptibility technique which became a more rapid and cost-effective compared to conventional methods. Increasing heavy metal contents in soils causes an increase in the magnetic mineral concentration. The study area is located in Al- Muthanna province, southeast of Iraq, and contains three cement plants, an oil refinery, bricks factories, and power plants. Fifty topsoil and subsoil samples (0-50 cm depth) were collected from five sites; Al-Jinoob cement plant (one site), Samawa oil refinery (two sites) and Al- Muthanna cement plant (two sites). In this study, magnetic properties of samples in vertical sections and levels of heavy metal elements; of selected samples from regions with different geological settings were compared. The heavy metals analysis included chromium (Cu), iron (Fe), nickel (Ni), copper (Cu), Arsenic (As) and lead (Pb), which could give indications of heavy metal pollution in soil. The highest magnetic susceptibility value (65.23 x10-8 m3kg-1) was recorded in Al-Muthanna cement plant (TSL-4) and the highest Cu concentration (602.57 ppm) was also recorded in Al-Muthanna cement plant (TSL-5-3). The results of magnetic properties show the dominance of coarse magnetite, which is supposed to have originated from pedogenic particles in natural soils, causing the positive correlation between magnetic susceptibility (Ï‡) and anhysteretic remanent magnetisation (ARM). According to the results of frequency dependent susceptibility ratio (Îºfd%), the magnetic particles showed an admixture of multi-domain and pseudo-single domain behaviour. Magnetic susceptibility and heavy metal analyses results indicated emissions from nearby industrial plants. X-ray fluorescence (XRF) was carried out for heavy metal analyses which supported our results. Results of this study demonstrate the suitability of applying magnetic techniques for assessing environmental situations.